Strengthening marketing promotion through digital marketing assistance using Google Business and business legality for MSMEs in Saptorenggo Village, Malang Regency - Nihayatu Aslamatis Solekah; Rangga Saputra; Farida Dwi Rahmawati; Fitri Ilma Wahyuni; Yuanggi Nur Wiria Tarita (Universitas Muhammadiyah Magelang, 2023)
This community service was conducted in Saptorenggo Village, Pakis District, Malang Regency. This program aims to increase digital marketing promotion through Google Business and business legality for MSMEs in Saptorenggo Village, Pakis District, Malang Regency. Participatory rural appraisal, which requires an active involvement of the community, is a model applied in this program. The implementation begins with mapping MSMEs in Saptorenggo Village that can become partners, and from the results of this mapping, the potential and needs of these MSMEs are known. Then, digital marketing was carried out for these MSMEs by creating a Google business point to increase the marketing reach of MSMEs in Saptorenggo Village and strengthen business legality for 9 MSMEs in Saptorenggo Village with the help of obtaining NIB, PIRT and halal certificates.